USEFULNESS OF AN ELISA KIT FOR THE DETECTION OF Histoplasma capsulatum ANTIGEN IN PATIENTS WITH AIDS - Arechavalia, Alicia; Bianchi, Mario; Messina, Fernando; Romero, Mercedes; Negroni, Ricardo; Santiso, Gabriela (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Histoplasmosis is a systemic mycosis frequently affecting patients infected with HIV, appearing as acute or subacute disseminated forms. Early diagnosis is simple when muco-cutaneous lesions are present; but in their absence the use of non-culture based methods is usually required presenting a fundamental challenge for the management and prognosis of this infection. The aim of this study was to analyze the sensitivity and specificity of an Elisa kit for the detection of the galactomannan antigen of Histoplasma capsulatum in different clinical samples. A total of 98 clinical samples obtained from different organic fluids were analyzed: 66 sera, 28 urine samples, 3 bronchoalveolar lavages and one cerebrospinal fluid. They corresponded to a total of 61 patients: 27 with histoplasmosis associated with AIDS, 7 histoplasmosis in nonreactive HIV individuals and 27 patients with other diseases but which were clinically similar to histoplasmosis. The sensitivity of the detection of the galactomannan antigen in serum of patients with histoplasmosis and AIDS was 76% and the specificity was 56%. In urine samples of this group of patients the sensitivity was 75%.